Young enterprise alumni as serial entrepreneurship / Arith Syakir Bunsu ... [et al.] - Bunsu, Arith Syakir; Daniel, Nur Zafika; Ramsa, Rizwanshah; -, Siti Nur Syazwanie; Empang Wan, Veronica (Perpustakaan Tun Abdul Razak, UiTM Sarawak, 2023)
Respondents were asked to choose their highest qualification from five categories. They were a highly educated group. Almost one in three had a first degree (32.1%), while 8.3% had a higher degree. The largest group chose A Levels as their highest qualification (40.8%) (Figure 4). Just one in ten chose GCSEs as their highest qualification. An alternative view to the importance of educational qualifications was provided via focus groups and interviews with Young Enterprise alumni.